The Effect of Personality on Career Aspirations of Secondary Schools’ Students in Khyber Pakhtunkhwa, Pakistan - Zeb, Alam; Ali, Arshad; Hussain, Mian Said (Journal of Development and Social Sciences, 2025)
The study investigated the effects of personality on career aspirations of secondary schools’ students. Study’s objectives were to; find out the effect of personality on career aspirations of secondary school students and develop strategies for career guidance of students. Study’s design was quantitative. Its population was 30439 students. Its sample of 380 students was selected with simple random sampling. A questionnaire was developed, validated and piloted for collecting data. Data were gathered with self-administered questionnaires and analyzed with mean scores, standard deviations and chi-square test. The study found the effect of students’ personality on career aspirations of students at secondary level. Factors of students’ personality, i.e. students’ interests, wills, aspirations, motivations and academic aptitudes affected students’ career aspirations. The study recommended availability of career guidance facilities in secondary schools. It also recommended assessment mechanism for identification of students’ interests and aptitudes for establishing appropriate career aspirations among secondary schools’ students.